PENGARUH PAD, SiLPA, DAU, DAN BELANJA MODAL TERHADAP PERILAKU OPORTUNISTIK DALAM PENYUSUNAN ANGGARAN DAERAH (Studi Kasus Kabupaten/Kota di Provinsi Jawa Tengah) (Students' Journal of Accounting and Banking, 2013)
Asymmetry of information between the executive and the legislature in the budget allocation process areas, especially when budget changes will be meaningless when the legislature to use its power advantage due to the mandate of Law No.22/1999 so hard to resist the executive legislative recommendation to allocate appropriate budget preferences. Law changes. 22/1999 to Law No.32/2004 on Regional Government seeks to reduce opportunistic behavior legislature. This study aims to examine and analyze: the effect of PAD to opportunistic behavior of local budgets constituent districts / municipalities in Central Java Province, influence on opportunistic behavior SiLPA budget drafters District / town in Central Java province, influence on opportunistic behavior constituent DAU budget Regency / Cities in Central Java Province. Effect of Capital Expenditure against budget opportunistic behavior regencies / cities in Central Java Province. The data used are secondary data obtained from the Directorate General of Fiscal Balance Central Java Province. The population in this study were all regencies / cities in Central Java province during the study period in 2009-2011. Sampling technique in this study using purposive sampling method. Based on the criteria laid out the sample there were 35 districts / cities. The analysis tools are using multiple linear regression. The results of this study indicate that the revenue (PAD), the General Allocation Fund (DAU) and Capital Expenditure positive effect Opportunistic Behavior Composer Regional Budget in regencies / cities in Central Java Province. Remaining Budget Calculation (SiLPA) negatively affect the behavior of Opportunistic Drafting Budget regency / city in Central Java Province.Keywords: Local Revenue (PAD), the Regional Budget Surplus Calculation (SiLPA), General Allocation Fund (DAU), Opportunistic Behavior Budget Drafting Area (OPA), and Capital Expenditures. Opportunistic behavior Budgetary Area (OPA).